Peran Orang Tua Dalam Pencegahan Stunting Melalui Program Sekolah Orang Tua Hebat Di Kelurahan Lakarsantri - Ellysia Eka Putri Agustina; Rizkya Dwijayanti (An-Najat, 2023)
Stunting is one of the world's nutritional problems, especially in poor and developing countries. Developmental delays are a problem because they are associated with an increased risk of morbidity and death, disruption of optimal brain development, resulting in motor development and development. The aim of this research is to find out whether the Great Parents School program is successful in providing education on stunting prevention patterns, development and educating parents about parenting patterns for early childhood. Considering that young children are in the prime period of childhood growth and development, improving family parenting skills can be a strategic step in maximizing the growing period to develop the next generation, as well as to find out the role of parents in preventing stunting in Lakarsantri Village. This research uses descriptive qualitative methods. Data collection techniques use interviews and documentation. In preventing stunting, Lakarsantri Subdistrict has made various efforts including posyandu, counseling or outreach by cadres, related Community Health Centers in the Great Parent School program to the community about the importance of the role of the family in supporting children's growth and development, so as to increase community awareness in overcoming the problem of stunting. , providing additional food to fulfill balanced nutrition in the form of eggs, bread, milk, as well as efforts to increase the role of parents in supporting children's growth and development, especially in terms of meeting children's nutritional and health needs and providing stimulation appropriate to the child's age.